RESEPSI GURU SEKOLAH DASAR TERHADAP PROGRAM GURUKU SBO TV - SEKARSARI, THERESIA ANDICKY (The Commercium, 2022)
Guruku SBO TV helps elementary school students in Surabaya to better understand the material directly by watching shows that act as an intermediary between teachers and the Surabaya City Dispendik and students. This study aims to find out how the reception of elementary school teachers' messages to the Guruku SBO TV program. This type of research is a qualitative research with an audience reception analysis method approach. The research uses constructivism paradigm. Data collection was done by interview and observation. The results of the study show that there are two categories of audiences in receiving Guruku SBO TV messages, namely the dominant audience of 2 informants and the negotiating audience of 6 informants. There are 5 message reception points in the dominant position and there are 3 message reception points in the negotiating position. 4 points agreed upon by the informants, e.g., 1) The Guruku's presenter is good, 2) fulfills the need for access to elementary education during the pandemic in Surabaya, 3) is easily accessible, 4) prays as a religious value and sings as an apperception. Guruku is good and interesting and has a contribution to the delivery of material which is constrained because the school is online. This research can be used as a study for other research on educational television broadcasts in collaboration with the Ministry of National Education, especially during the pandemic.